2019
DOI: 10.1186/s12906-019-2463-2
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of the hydro-ethanol extract of Senecio serratuloides DC in rats

Abstract: Background Senecio serratuloides DC is used in folk medicine for treating hypertension, skin disorders, internal and external sores, rashes, burns and wounds. This study aimed at investigating the antihypertensive effects of the hydroethanol extract of S. serratuloides (HESS) in N-Nitro-L-arginine methyl ester (L-NAME) induced hypertension in rats. Methods: Acute toxicity of HESS was first determined to provide guidance on doses to be used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Some documented pharmacological applications of medicinal plants include antioxidant [4], anti-inflammatory [5], hypolipidemic [6], antidiarrheal [7], anti-proliferative [8,9], antihypertensive [10], neuroprotective [11], hepatoprotective [12], nephroprotective [13,14], antidiabetic [15], anti-ulcer [16,17], gastroprotective [18,19], haematopoietic [20] and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Some documented pharmacological applications of medicinal plants include antioxidant [4], anti-inflammatory [5], hypolipidemic [6], antidiarrheal [7], anti-proliferative [8,9], antihypertensive [10], neuroprotective [11], hepatoprotective [12], nephroprotective [13,14], antidiabetic [15], anti-ulcer [16,17], gastroprotective [18,19], haematopoietic [20] and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Senecio serratuloides is also used singly or in combination with other plants to treat wounds such as cuts, internal and external sores (including those resulting from sexually transmitted infections), burns, swollen gums and chest pain (De Wet, Nciki, & van Vuuren, 2013;De Wet, Nzama, & Van Vuuren, 2012;Fawole et al, 2010;Gould, Penny, Patel, & Candy, 2015). A study in our laboratory reported the antihypertensive effect of the hydoethanolic extract of S. serratuloides (Tata et al, 2019). The plant has also been reported to have phenols, tannins, flavonoids, and gallotannins and to possess antiinflammatory, anticholinesterase, antioxidant, and wound healing properties (Fawole et al, 2010;Gould et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Then, AEAL antihypertensive effect might be due to its antioxidant properties since it is well document that the principal mechanisms in L-NAME-induced hypertension is oxidative stress but also to AEAL capacity to inhibit PDEs localized in the vascular smooth muscle cells. 9 , 36 , 60 , 67 , 68 Indeed, previous studies indicate that extract from Anogeissus leiocarpa has confirmed this potential antioxidant activity. 69–71 …”
Section: Discussionmentioning
confidence: 61%